Design of Integrated Information System Architecture for BUMDES Management Based on TOGAF ADM - Muhammad Ibrahim Adham Karim; Septi Andryana (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2025)
Enhancing the accountability and effectiveness of Village-Owned Enterprises (BUMDes) requires an information-system architecture that aligns business processes with public reporting needs. Prior public-sector studies often remain conceptual and rarely demonstrate an end-to-end path from stakeholder requirements to user-validated architectural design. This study proposes a strategy grounded in Enterprise Architecture using the TOGAF-ADM approach. A qualitative, design-oriented method was employed through policy document analysis, stakeholder interviews/observations, and a SWOT assessment feeding the Architecture Vision. The outcome comprises core artifacts across the Business-Data-Application-Technology layers that specify service objectives, information needs, and application support for BUMDes key processes. User acceptance testing indicates a 97% acceptance rate, evidencing strong alignment between the design and operational/reporting requirements. The study contributes a replicable architectural strategy as a foundation for developing integrated information systems in BUMDes settings. Limitations include a single-case context; future work should test generalizability across varying organizational scales and institutional conditions.